Optimal economic thickness of various insulation materials for different orientations of external walls considering the wind characteristics - Axaopoulos, Ioannis; Axaopoulos, Petros J.; Panayiotou, Gregoris; Kalogirou, Soteris A.; Gelegenis, John Joachim (My University, 2015)
The economic optimum insulation thickness of various insulation materials for external walls of different topologies and orientations was determined, taking into account the heating and cooling period and the speed and direction of the wind. Annual heating and cooling transmission loads are being calculated based on transient heat flow through the external walls and by using hourly climatic data for an entire typical meteorological year of the city of Larnaca, Cyprus. The available wind speed and direction data have been statistically analysed for the assessment of the prevalent wind directions in the area. The optimisation is carried out using the Life Cycle Savings method. According to the results, the north-facing walls offer the greatest economic benefit compared to the corresponding wall types of different orientation, regardless of the insulation thickness. They also have the shortest payback period. The optimum insulation thickness calculated for any wall topology and orientation varies from 4.25 cm to 15.5 cm, and the payback period varies from 5.47 years to 12.11 years.
Keywords: Wind direction; Life cycle saving; TRNSYS; Cooling load